2013
DOI: 10.1002/wsbm.1240
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying neuronal synaptic plasticity: systems biology meets computational neuroscience in the wilds of synaptic plasticity

Abstract: Interactions among signaling pathways that are activated by transmembrane receptors produce complex networks and emergent dynamical behaviors that are implicated in synaptic plasticity. Temporal dynamics and spatial aspects are critical determinants of cell responses such as synaptic plasticity, though the mapping between spatio-temporal activity pattern and direction of synaptic plasticity is not completely understood. Computational modeling of neuronal signaling pathways has significantly contributed to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Synaptic plasticity is the changes in synaptic strength (the structures or the functions) produced by the diverse-stimulation procedures in vitro and in vivo [43]. Whitlock et al [44] reported that synaptic plasticity is an important mechanism that underlies long-term memory storage.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic plasticity is the changes in synaptic strength (the structures or the functions) produced by the diverse-stimulation procedures in vitro and in vivo [43]. Whitlock et al [44] reported that synaptic plasticity is an important mechanism that underlies long-term memory storage.…”
Section: Discussionmentioning
confidence: 99%
“…The model contains two compartments ( Fig 1 ). The sub-membrane compartment comprises the volume of cytosol directly below the plasma membrane to a distance of 120nm [ 80 ], and consists of three sub-compartments: postsynaptic density (PSD), endocytic zone (EZ) and extra-synaptic area. The sub-endosome compartment is assumed to occupy the same volume as the sub-membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular plasticity represents a fundamental parameter in brain functioning that permits rapid adaptational responses of neural circuits to current need of the organism, thereby supporting complex brain functions like learning and memory by providing the building blocks for the formation of lasting changes at higher levels of neural organization (Ziv and Brenner 2018;Minatohara et al 2016;Diekelmann and Born 2010). Hence, mechanisms of molecular plasticity are essential in supporting maintained changes in synaptic transmission that underlie learning and memory (Shonesy et al 2014;Blackwell and Jedrzejewska-Szmek 2013;Elgersma and Silva 1999;Colbran 2015;Kotaleski and Blackwell 2010). Inversely, increased ability for plastic changes at synaptic, cellular and higher levels of brain organization is indicative of an increased ability for plastic changes at the molecular level (Koehl 2015).…”
Section: Introductionmentioning
confidence: 99%